Efeitos da estimulação elétrica neuromuscular nas circuitarias medulares inibitórias de sujeitos crônicos após acidente vascular cerebral - Motta-Oishi, Anna Amélia Pereira da [UNESP] (2014)
The goal of this study was to analyse the effects of a neuromuscular electrical stimulation protocol considering the medullary inhibitory patterns, function and spasticity in 17 spastic hemiplegic subjects. These patients were divided in two groups. In the training group, the subjects received 30 minutes of the neuromuscular electrical stimulation on the tibialis anterior muscle of the affected side during 30 sessions. In each session it was considered a frequency of 30 Hz, pulse-width of 250 ms, 6 s on and off time, and the intensity depending on the threshold of the muscle contraction and the patient tolerance. In the control group zero intensity electrical stimulation was adopted. Before and final of the thirty sessions, reciprocal inhibition and pre synaptic inhibition were studied by using the H-reflex conditioning test while the homosynaptic depression was investigated trough of the H-reflex. In addition, the distance of the 2-minute walk test, motor recovery in the lower limb subscale of Fugl-Meyer, and spasticity according to the Ashworth modified scale were also measured. The results of the training group showed a statistically significant increase of the homosynaptic depression of 12.30 % (± 9.89 %) p = 0.03, the distance of 16.8 meters (± 9.17) p = 0.00, and the points in the Fugl-Meyer scale of 2.20 (± 1.93) p = 0.00...